2015
DOI: 10.1542/hpeds.2014-0135
|View full text |Cite
|
Sign up to set email alerts
|

The Practice Patterns of Recently Graduated Internal Medicine–Pediatric Hospitalists

Abstract: RESULTS:Forty-nine program directors (62%) completed the survey and provided data on 1042 graduates from 46 programs. Of those graduates, 26.4% (n = 275) practice as hospitalists, and none had completed an HM fellowship. Approximately two-thirds (65%) of med-peds hospitalists provide care to hospitalized children and adults, with one-third providing care solely to hospitalized adults. Approximately one-half (53.5%) have an appointment with a medical school and roughly one-quarter (28%) practice in a freestandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…3 Our survey queried practicing physicians, thus capturing a more comprehensive evaluation of the current workforce. [5][6][7] In keeping with current medical workforce trends, our survey showed many differences among physicians in practice fewer than 10 years vs individuals practicing longer. Newer med-peds physicians are increasingly choosing nonprimary care careers and are less likely to consider themselves primary care providers compared with physicians who trained previously, mirroring trends in medical students, 10,11 categorical pediatric, 12 and internal medicine residency graduates.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…3 Our survey queried practicing physicians, thus capturing a more comprehensive evaluation of the current workforce. [5][6][7] In keeping with current medical workforce trends, our survey showed many differences among physicians in practice fewer than 10 years vs individuals practicing longer. Newer med-peds physicians are increasingly choosing nonprimary care careers and are less likely to consider themselves primary care providers compared with physicians who trained previously, mirroring trends in medical students, 10,11 categorical pediatric, 12 and internal medicine residency graduates.…”
Section: Discussionsupporting
confidence: 57%
“…Of residency graduates in the last 5 years who practice primarily in the outpatient setting, 19% provide some type of inpatient care. 7 Our study contained several limitations. First, we sampled only about 75% of the estimated med-peds workforce and had a modest response rate.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…More than one-quarter of recent combined medicine-pediatrics graduates pursued hospital medicine positions, with more than two-thirds of those caring for both adult and pediatric inpatients. 7 In a survey of 112 pediatric hospitalist programs in 2006 and 2007, hospitalist directors reported that 46% of their physicians were relatively newly employed (ie, for <3 years) with an average duration of employment of 63 months. 8 Hospitalists serve as role models for medical learners on inpatient rotations, and provide hospital administrative leadership in programs such as quality, safety, and electronic health systems.…”
Section: Hospital Medicinementioning
confidence: 99%